Impact of COVID-19 lockdown on psychosocial factors, health, and lifestyle in Scottish octogenarians: The Lothian Birth Cohort 1936 study. - Adele M Taylor; Danielle Page; Judith A Okely; Janie Corley; Miles Welstead; Barbora Skarabela; Paul Redmond; Tom C Russ; Simon R Cox (PLoS ONE)
Background Little is known about effects of COVID-19 lockdown on psychosocial factors, health and lifestyle in older adults, particularly those aged over 80 years, despite the risks posed by COVID-19 to this age group. Methods Lothian Birth Cohort 1936 members, residing mostly in Edinburgh and the surrounding Lothians regions in Scotland, mean age 84 years (SD = 0.3), responded to an online questionnaire in May 2020 (n = 190). We examined responses (experience and knowledge of COVID-19; adherence to guidance; impact on day-to-day living; social contact; self-reported physical and mental health; loneliness; and lifestyle) and relationships between previously-measured characteristics and questionnaire outcomes. Results Four respondents experienced COVID-19; most had good COVID-19 knowledge (94.7%) and found guidance easy to understand (86.3%). There were modest declines in self-reported physical and mental health, and 48.2% did less physical activity. In multivariable regression models, adherence to guidance by leaving the house less often associated with less professional occupational class (OR = 0.71, 95%CI 0.51-0.98) and poorer self-rated general health (OR = 0.62, 95%CI 0.42-0.92). Increased internet use associated with female sex (OR = 2.32, 95%CI 1.12-4.86) and higher general cognitive ability (OR = 1.53, 95%CI 1.03-2.33). Loneliness associated with living alone (OR = 0.15, 95%CI 0.07-0.31) and greater anxiety symptoms (OR = 1.76, 95%CI 0.45-1.24). COVID-19 related stress associated with lower emotional stability scores (OR = 0.40, 95%CI 0.24-0.62). Decreased physical activity associated with less professional occupational class (OR = 1.43, 95%CI 1.04-1.96), and lower general cognitive ability (OR = 0.679, 95%CI 0.491-0.931). Conclusions Characteristics including cognitive function, occupational class, self-rated health, anxiety, and emotional stability, may be related to risk of poorer lockdown-related psychosocial and physical outcomes.